Soft Diplomasi Jepang Melalui Anime dan Manga Untuk Meningkatkan Nation Branding Jepang - Garmabar, Padlika; Rifai, Maulana; Hakim, Fadhlan Nur (Universitas 17 Agustus 1945 Jakarta, 2024)
Globalization makes it easy to access incoming information that can be accessed from anywhere and influences international community relations. Japan uses its popular culture to improve its nation branding. Popular culture includes anime and manga as part of soft diplomacy. This research uses qualitative methods with data obtained from books, documents, journals and other works. Data collection techniques use documentation studies, data will be processed and concluded to find answers to the problems faced. The results of this research can be said that Japan has succeeded in increasing its nation branding through anime and manga in Indonesia. The widespread distribution of anime and manga in Indonesia is one of the factors in the success of the Japanese government in influencing Indonesian people to get to know Japanese culture. Other successes can be seen from the many Japanese-themed festivals held by the official, private and unofficial government. Japan has succeeded in creating a view shown in anime and manga which shows that Japan is a country rich in cultural heritage. This success also increases visits from Indonesian people who travel to Japan every year, even though it has experienced a decline due to the Covid 19 pandemic. Thus, Japan can be said to be successful in its achievements in improving its country's nation branding.